LINES ABOUT CONSTITUTIONAL HEALING PROBLEM - Borges de Oliveira, Emerson Ademir (Revista de Direito Brasileira, 2020)
Can the Constitution be healed? The aim of this article is the answer on how to deal with offenses committed in the face of the Constitution which are built on consolidated factual situations. Often the simple declaration of unconstitutionality, either from the beginning, the theory of nullity, or for the future, in annulability theory, or in conjunction both with the temporal modulation effects will not show positive responses to the constitutional offense. On the other hand, the recognition of unconstitutionality, although for the future, could lead to more harmful economic, political, social and legal effects than maintaining the offensive act. Sometimes the theory of constitutionalising supervening can respond appropriately, with the change of the constitutional paradigm. But what to do when the Constitution is even changed? The methodology for the development work is eminently literature and case law.